Associations between health behaviours and health related fitness. Issue 2 (June 1996) - Shephard, R J; Bouchard, C
Abstract : OBJECTIVE: To examine relations between health behaviours and health related fitness. METHODS: Subjects were a convenience sample of 350 healthy adults (172 men, 178 women). Covariance analysis adjusted data for significant influences of age and socioeconomic status. Obesity was assessed by anthropometry and body density. Cardiovascular fitness was assessed and various metabolic measurements were made. Questionnaires on physical activity and health related behaviours were completed. RESULTS: Cigarette abstinence was associated with a small abdominal circumference (men) and a low trunk/extremity skinfold ratio (women). Obesity indices (body mass index, total skinfolds, percent fat, and abdominal circumference) were negatively associated with perceived fitness. Leisure activity and exercise frequency were also negatively linked to some obesity indices. Blood glucose, cholesterol, HDL-cholesterol, and triglycerides were favourably influenced by perceived activity, exercise frequency, and perceived fitness, but not by exercise intensity. Abstinence from coffee was associated with a low cholesterol/HDL ratio (men only). Principal component, discriminant, and multiple logistic regression analyses showed only weak clustering of habitual physical activity with other positive health behaviours. CONCLUSIONS: Although multiphasic health promotion programmes are economical, favourable interactions between individual programme elements seem likely to be quite limited.